Future Generations in Climate Litigation: Early Whispers of an Intergenerational Law? - Drigo, Alessandro; Justus Liebig University Giessen (My University, 2024)
The “migration” of Future Generations from a moral to a judicial context represents a captivating development in contemporary legal discourse. Recent years have seen a surge in courts across various nations addressing the intersection of future generations and climate litigation. This nexus, far from being coincidental or sporadic, epitomizes a deeper societal and legal dilemma that necessitates a nuanced articulation for effective resolution. The main objective of this Article is to provide preliminary insights for contextualizing this legal evolution. Initially, the Article delineates the journey towards social legitimacy of climate science. Subsequently, it examines the impact of this social legitimation on judicial rulings, particularly observing an emerging trend in climate litigation to expand the temporal scope of legal relevance. The Article culminates in an exploration of the possible interplay between the legal significance of future generations and the extension of the law’s temporal horizon. This conjectural postulation is substantiated through select historical precedents.
Keywords: ddc:340